Sonographic evaluation of masseter muscle thickness in bruxist and non-bruxist subjects - Najm, Areej A (Journal of Baghdad College of Dentistry, 2014)
Background: Masseter muscle is a jaw closing muscle of the mandible involved in Para functional habits; which include lip and cheek chewing, fingernail biting, and teeth clenching or bruxism which can be classified as awake or sleep bruxism. Patients with sleep bruxism are three to four times more likely to experience jaw pain and limitation of movement than people who do not experience sleep bruxism. The aim of this study is to measure the thickness of the masseter muscle in bruxist subjects and compare it with non-bruxist subjects by using sonography. Materials and Method: Forty Iraqi subjects with age ranged (20-40) divided into two groups according to the presence of bruxism. Clinical examination was made and masseter muscle thickness measured for both groups using sonography. Results: For bruxist subjects the mean thickness of masseter muscle in relaxation and clenching were (11.7 ± 1.4 mm) and (16.4 ± 1.3 mm). For non bruxist subjects were (11.2 ± 0.4 mm) and (13 ±0.3 mm) respectively. There was an extremely high statistical significant difference in masseter muscle thickness under clenching between bruxist and non bruxist subjects ( it was higher in bruxist group). Masseter muscle thickness under relaxation was significantly lower than that under clenching for both groups. Also there was a positive correlation between masseter muscle thickness and muscle function in bruxism situation. Conclusion: Masseter muscle in bruxist subject was thicker when compared to non-bruxist subject. Masseter muscle thickness was found to be positively correlated with increasing muscle function. The findings of this study indicate that the functional capacity of the masseter muscle affected by bruxism and may be considered as one of the factors influencing muscle thickness.